2017
DOI: 10.1016/j.ibror.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prosaposin and its receptors in the rat cerebellum after kainic acid injection

Abstract: Prosaposin (PSAP), a highly conserved glycoprotein, is a precursor of saposins A–D. Accumulating evidence suggests that PSAP is a neurotrophic factor that induces differentiation and prevents death in a variety of neuronal cells through the active region within the saposin C domain both in vivo and in vitro. Recently, GPR37 and GPR37L1 were recognized as PSAP receptors. In this study, we examined the alteration in expression of PSAP and its receptors in the cerebellum using rats injected with kainic acid (KA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The specificity of the GPR37 and GPR37L1 antibodies used in this study was examined in the mice cerebellum by western blotting. A single immunoreactive band, similar to the report by Li et al [ 26 ], was observed for each antibody ( Fig. 1
Fig.
…”
Section: Resultssupporting
confidence: 86%
“…The specificity of the GPR37 and GPR37L1 antibodies used in this study was examined in the mice cerebellum by western blotting. A single immunoreactive band, similar to the report by Li et al [ 26 ], was observed for each antibody ( Fig. 1
Fig.
…”
Section: Resultssupporting
confidence: 86%
“…Population 5 (mint; top genes NHLH1, CNTN2, DAPL1, ATOH1, TCF4, MIAT ) expressed GC precursor markers NEUROD2, NEUROD6, PAX3, MEIS1, DCC and NFIB consistent with RL derivatives. Population 6 (teal; top genes TRIB3, HSPA9, DDIT3, NUPR1, EIF1 & KCNG1 ) expressed markers consistent with PNs including PSAP 26 , CALCB 27 , ALDOA, FTL , FTH1 , and AARS . Population 7 (blue; top genes RSPO3, RSPO1, RSPO2, CNTNAP2, MASP1, PLS3 ) also strongly expressed the genes SPARC, S100B, LMX1A, HES1 and TTR , consistent with roof plate cells.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of higher levels of PSAP in PV-positive GABAergic inhibitory interneurons and their axons around pyramidal neurons suggested the axonal transport of PSAP [24,25] (Figure 1h-i). Similarly, PSAP was strongly expressed in the Purkinje cells and interneurons of the cerebellum of KA-injected rats [26]. These findings provide insights into the role of PSAP in alleviating the neural damage caused by KA.…”
Section: Psap Rescues Neurons From Damage Induced By Neurotoxic Agentsmentioning
confidence: 58%